Konstruksi Pemahaman Mahasiswa PAI UIN Aceh tentang Autophagy dalam Puasa Ramadhan - Saputri, Tessa Amelia; Hayati, Cut Intan (Desultanah: Journal Education and Social Science, 2026)
Ramadan fasting not only has a spiritual dimension, but is also related to the body's biological processes, one of which is autophagy, which is the mechanism of cleansing and regenerating cells. This study aims to analyze the perception of Islamic Religious Education (PAI) students on the relationship between Ramadan fasting and the concept of autophagy. This study uses a qualitative approach with an in-depth and semi-structured interview method for five PAI students of UIN Ar-Raniry Banda Aceh who were selected through purposive sampling and snowball sampling. The data was analyzed through a thematic coding process by identifying the main themes, core quotes, and interpretation of the informant's answers. The results of the study showed that students had a fairly good understanding of the relationship between fasting and autophagy. Five main themes were found, namely fasting as a trigger for autophagy, the suitability of spiritual values with biological benefits, the importance of diet during fasting, the balance between worship and health, and fasting as a practice that has scientific benefits. Students view fasting not only as a religious obligation, but also as a biological mechanism that helps the process of cleansing cells and maintaining the health of the body. In addition, students see a harmony between Islamic teachings and the development of modern science in explaining the benefits of fasting for physical, mental, and spiritual health. This research contributes to strengthening the interdisciplinary study between Islamic education and health sciences through an integrative approach between religion and science. The findings of the study also provide implications for the development of Islamic Religious Education learning that is more contextual and holistic. However, this study is still limited to a small number of informants so further research is recommended to involve a wider range of participants and a mixed methods approach